Pop internationalism - Krugman, Paul (MIT Press, 1996)
Krugman explains what real economic analysis is. He discusses economic terms and measurements, like "value-added" and GDP, in simple language so that readers can understand how pop internationalists distort, and sometimes contradict, the most basic truths about world trade